1996
DOI: 10.1104/pp.110.2.501
|View full text |Cite
|
Sign up to set email alerts
|

The Auxin Transport Inhibitor N-(1-Naphthyl)phthalamic Acid Elicits Pseudonodules on Nonnodulating Mutants of White Sweetclover

Abstract: The collection of symbiotic (sym) mutants of white sweetclover (Melilotus alba Desr.) provides a developmental sequence of mutants blocked early in infection or nodule organogenesis. Mutant phenotypes include non-nodulating mutants that exhibit root-hair deformations in response to Rhizobium meliloti, mutants that form ineffective nodules lacking infection threads, and mutants that form infection threads and ineffective nodules. Mutant alleles from both the sym-1 and the sym-3 loci exhibited a non-nodulating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
34
0
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 37 publications
(64 reference statements)
8
34
0
4
Order By: Relevance
“…In Arabidopsis, auxin gradients needed for lateral root initiation rely on a functional auxin transport system (Benkovà et al, 2003), which might suggest that nodule development depends on the auxin transport mechanisms of their hosts. This suggestion is supported by the observation that external application of synthetic auxin transport inhibitors to roots inhibits nodulation (van Noorden et al, 2006), although in some legumes, long-term application of auxin transport inhibitors can induce nodule-like structures (Hirsch et al, 1989;Wu et al, 1996). It is likely that temporary inhibition of polar auxin transport at the infection site is a prerequisite for indeterminate nodule formation, as rhizobia and purified Nod factors inhibit the auxin response in white clover roots expressing an auxinresponsive GUS reporter below the site of inoculation, similar to the action of synthetic auxin transport inhibitors (Mathesius et al, 1998a).…”
Section: Rhizobia Alter Host Auxin Transportsupporting
confidence: 51%
“…In Arabidopsis, auxin gradients needed for lateral root initiation rely on a functional auxin transport system (Benkovà et al, 2003), which might suggest that nodule development depends on the auxin transport mechanisms of their hosts. This suggestion is supported by the observation that external application of synthetic auxin transport inhibitors to roots inhibits nodulation (van Noorden et al, 2006), although in some legumes, long-term application of auxin transport inhibitors can induce nodule-like structures (Hirsch et al, 1989;Wu et al, 1996). It is likely that temporary inhibition of polar auxin transport at the infection site is a prerequisite for indeterminate nodule formation, as rhizobia and purified Nod factors inhibit the auxin response in white clover roots expressing an auxinresponsive GUS reporter below the site of inoculation, similar to the action of synthetic auxin transport inhibitors (Mathesius et al, 1998a).…”
Section: Rhizobia Alter Host Auxin Transportsupporting
confidence: 51%
“…That is most likely to be the regulation of the hormone level, in particular that of auxin, by acting at the level of its synthesis and/or transport. These indirectly affect nodule formation (Kefford et al, 1960;Hunter, 1987;1989;Hirsch et al, 1989;Fukuhara et al, 1994;Wu et al, 1996) and the partitioning of photosynthates (Brenner and Cheikh, 1995). This is further supported by the synergistic response observed to HBR and auxin (Mandava, 1988).…”
Section: Resultssupporting
confidence: 55%
“…Indeed, application of polar auxin transport inhibitors such as NPA and 2,3,5-triiodobenzoic acid (TIBA) can induce spontaneous nodules in some legumes (Allen et al 1953;Hirsch et al 1989;Wu et al 1996;Rightmyer and Long 2011). It has been shown that some genes transcriptionally controlled by both nodulation and auxin transport inhibitors might be important for nodule initiation (Rightmyer and Long 2011).…”
Section: More Root Organs: Nodule Formation Is Enhanced By Exogenous mentioning
confidence: 99%